Linkage analysis of multiplex Caribbean Hispanic families loaded for unexplained early‐onset cases identifies novel Alzheimer's disease loci. Issue 1 (27th August 2018) - Cheng, Rong; Tang, Min; Martinez, Izri; Ayodele, Temitope; Baez, Penelope; Reyes‐Dumeyer, Dolly; Lantigua, Rafael; Medrano, Martin; Jimenez‐Velazquez, Ivonne; Lee, Joseph H.; Beecham, Gary W.; Reitz, Christiane
Abstract: Introduction: Less than 10% of early‐onset Alzheimer's disease (EOAD) is explained by known mutations. Methods: We conducted genetic linkage analysis of 68 well‐phenotyped Caribbean Hispanic families without clear inheritance patterns or mutations in APP, PSEN1, and PSEN2 and with two or more individuals with EOAD. Results: We identified 16 (logarithm of odds > 3.6) linked regions, including eight novel loci for EOAD (2p15, 5q14.1, 11p15.1, 13q21.22, 13q33.1, 16p12.1, 20p12.1, and 20q11.21) and eight regions previously associated with late‐onset Alzheimer's disease. The strongest signal was observed at 16p12.1 (25 cM, 33 Mb; heterogeneity logarithm of odds = 5.3), ∼3 Mb upstream of the ceroid lipofuscinosis 3 ( CLN3 ) gene associated with juvenile neuronal ceroid lipofuscinosis (JNCL), which functions in retromer trafficking and has been reported to alter intracellular processing of the amyloid precursor protein. Discussion: This study supports the notion that the genetic architectures of unexplained EOAD and late‐onset AD overlap partially, but not fully.